Towards understanding Lepidocyrtus Bourlet, 1839 (Collembola, Entomobryidae) I: diagnosis of the subgenus Setogaster, new records and redescriptions of species - Mateos, Eduardo (Zootaxa, 2015)
The taxonomic status of the subgenera of Lepidocyrtus Bourlet is confused. Currently ten subgenera are recognised but their separation, using the existing set of diagnostic characters, is not clear. Collections over the last forty years have shown that species of Setogaster Salmon, originally described as a genus (Trichogaster Handschin) and currently considered a subgenus of Lepidocyrtus, are common and widespread in Australia. The diagnostic characters of Setogaster, as given by Handschin, are: 1) the basal mucronal spine with spinelet; 2) lack of scales on antennae, legs, ventral tube and dorsal region of manubrium; and, for some species, 3) tufts of long filaments laterally on abdomen III. These three diagnostic characters for Setogaster are shared with some other subgenera, making their delimitation unclear. We provide here an array of new characters that are associated with Handschin’s characters which separate Setogaster from all European species of the subgenera Lanocyrtus and Lepidocyrtus s. str. On this basis we define subgenus Setogaster more in detail, redescribe some species in the subgenus, corroborate the presence of the subgenus in many Australian localities, and confirm three records of exotic, introduced species in Australia. Lepidocyrtus nigrofasciatus Womersley, Lepidocyrtus praecisus Schött, and the Hawaiian Lepidocyrtus kuakea Christiansen & Bellinger, are placed in Setogaster subgenus; Lepidocyrtus (Trichogaster) pallida Salmon from Singapore is placed in the subgenus Acrocyrtus; Merapicyrtus Yoshii & Suhardjono is considered a synonym of Setogaster.